Development and growth in the Mexican economy an historical perspective - Moreno-Brid, Juan Carlos; Ros, Jaime (Oxford : Oxford University Press, 2009)
This work provides an overview of Mexico's economic development since independence identifying its binding constraints in different periods and the ways in which economic policies have tried to remove them.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Mexico -- Economic conditions -- 19th century; Mexico -- Economic conditions -- 20th century